Legal Protection for Holders of Ownership Right Certificates Against Non-Procedural Land Execution - Alluvian, Laksmana; Gibran Abdul Jabar Maulani; Gavin Adiva Ramudia (Fakultas Hukum Universitas Airlangga, 2025)
Land disputes frequently arise due to population growth and increasing land demands, where non-procedural land executions can harm holders of Certificate of Ownership (SHM). Although land certificates serve as strong proof of ownership under Article 19 of the Basic Agrarian Law (UUPA) and Article 32 of Government Regulation No. 24 of 1997, legal certainty for landowners remains incomplete. This study aims to analyze the legal protection for SHM holders facing non-procedural land executions. The research employs a normative juridical method with statutory and conceptual approaches, examining relevant laws and legal doctrines. The findings indicate that SHM holds strong evidentiary power as long as its physical and juridical data align with land survey documents and land registers. However, land executions must follow proper procedures, starting with an execution request and a court warning, while adhering to principles of legal certainty and justice. SHM holders subjected to non-procedural executions can file an objection to the execution or a lawsuit for Unlawful Acts (PMH) under Article 1365 of the Civil Code. Case, such as the forced eviction in Tambun (2025), highlight the importance of proper legal procedures. In conclusion, while SHM provides legal protection, measures such as execution objections and PMH lawsuits are necessary to safeguard landowners' rights. This study emphasizes the need for compliance with execution procedures and the protection of certificate holders to ensure legal certainty.